Claudins in ovarian cancer: emerging biomarkers and therapeutic targets - Lubna Therachiyil (4246156) (2025)
Tight junctions (TJ) comprise protein complexes that help with the movement of ions and molecules through the paracellular pathway, thus maintaining both epithelial and endothelial integrity. The TJ proteins are diverse and include claudins, occludins, tricellulins, cingulins, and junctional adhesion molecules (JAM). Claudins are transmembrane proteins that serve as critical components of TJs in epithelial and endothelial cells. The human genome comprises 23 claudin genes, with 27 transmembrane domains recognized in mammals. Ovarian cancer (OC) is the most lethal form of all gynecologic malignancies worldwide, characterized by poor prognosis and a recurrence rate of up to 75%. In OC, several claudins are overexpressed relative to normal ovarian tissue. These elevated expression observed among OC subtypes indicates their potential utility as diagnostic biomarkers. Claudins represent potential targets for innovative therapeutic strategies. Though their exact involvement in OC is still not well understood, they are believed to be crucial for cancer invasion and therapy resistance. Recent studies show that claudins are involved in the EMT pathway and ERK, enlightening the effect of claudins in drug resistance. Clostridium perfringens enterotoxin (CPE) demonstrates potential as a therapy targeting claudins, specifically claudin-3 and −4, which serve as receptors for this toxin. Despite these advancements, challenges remain in comprehensively understanding claudin functions and in the development of effective claudin-targeted therapies. This review consolidates existing knowledge regarding claudins in OC, focusing on their expression patterns, biological functions, diagnostic and prognostic significance, and therapeutic implications. A thorough understanding of claudins in OC establishes a basis for enhancing diagnostic, predictive, and therapeutic approaches, which may result in improved therapy outcomes. Other Information Published in: Tissue Barriers License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/21688370.2025.2539026